Facile preparation of a Ag/graphene electrocatalyst with high activity for the oxygen reduction reaction. Issue 26 (20th April 2020) - Ren, Yaqi; Zhao, Hong; Li, Jianpeng; Wang, Rui; Wei, Zhaohuan
Abstract : Ag/graphene composite with small and well-dispersed Ag nanoparticles anchored onto the surface of graphene was prepared via a simple route from a disposal paper-cup, and exhibited superior electrocatalytic property for the oxygen reduction reaction. Abstract : Small Ag nanoparticles are well dispersed onto graphene sheets via a simple and environmentally friendly route using disposable paper-cups. The obtained Ag/graphene materials exhibit much higher catalytic activity for the oxygen reduction reaction than the conventional Ag/graphene catalyst does in alkaline media.